Preparation method of monatomic catalyst with Ir loaded on defect-rich titanium oxide nanorod carrier

By loading the single-atom catalyst of Ir on the titanium oxide nanorod support and synergistic activation of oxygen vacancies, the problem of high usage and low activity of Ir-based catalysts in acidic oxygen evolution reactions is solved, and an efficient and economical catalytic effect is achieved.

CN119824431APending Publication Date: 2025-04-15TOYOTA JIDOSHA KK +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311331290.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-13
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

When the existing Ir-based catalyst is used in the PEM water electrolytic cell for acidic oxygen evolution reaction, there are problems such as scarce resources of precious metal Ir, expensive, high usage load, and low mass activity.

Method used

The Ir single atom catalyst is supported on the defect-rich titanium oxide nanorod support, and the Ir single atom is synergistically activated by oxygen vacancies to enhance the activity of the catalyst.

Benefits of technology

The efficient catalytic oxygen evolution reaction under acidic conditions is achieved, which reduces the use of precious metal Ir and improves the activity and cost-effectiveness of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824431A_ABST
    Figure CN119824431A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an Ir monatomic catalyst loaded on a defect-rich titanium oxide nanorod carrier, the catalyst prepared by the method and application of the catalyst. The preparation method comprises the following steps: (S1) preparing the titanium oxide nanorod carrier rich in defects; and (S2) preparing the supported catalyst. In the catalyst provided by the invention, Ir single atoms cooperate with oxygen vacancies to activate the activity of inert Ti sites, so that the intrinsic activity of the catalyst is improved. Moreover, the catalyst provided by the invention has the advantages of simple preparation method, safety, easiness in operation and suitability for large-scale stable preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of new energy materials, and in particular to a method for preparing an Ir single atom doped synergistically oxygen vacancy titanium oxide nanorod carrier to promote oxygen evolution in acidic water electrolysis. Background Art

[0002] Proton exchange membrane (PEM) water electrolyzers are of great significance for the storage and conversion of renewable energy. Acidic oxygen evolution reaction (OER) is one of the main obstacles hindering the practical application of PEM water electrolyzers. The development of highly active, cost-effective and durable electrocatalysts is essential to reduce the high kinetic barrier of OER to achieve higher reaction kinetics. At present, Ir-based catalysts are the main OER electrocatalysts known for industrial applications in PEM. However, this type of catalyst has problems such as scarce resources of precious metal Ir, high price, high usage loading, and low mass activity. Therefore, further improving the OER performance of Ir-based catalysts and reducing the loading of precious metal Ir have become the focus and challenge of current research. Studies have shown that single atoms with maximum atomic utilization can effectively improve catalyst activity, reduce the amount of precious metals used and catalyst costs. Metal oxides that are stable under acidic conditions (such as TiO2, MnO2, WO3, Nb2O5) have been reported to be used as acidic OER catalyst supports. Among them, TiO2 has become one of the main candidates for acidic OER catalyst supports due to its low cost, availability, and stability in acidic and oxidizing environments. However, it is a challenge to load Ir single atoms on the TiO2 surface and improve the acidic OER activity. Summary of the invention

[0003] The present invention solves the problems of high noble metal loading, low atomic utilization and low catalytic activity, and provides a method for preparing an Ir single atom doped synergistic oxygen vacancy titanium oxide nanorod-promoted acidic water electrolysis oxygen evolution catalyst.

[0004] To achieve the above objectives, the present invention provides a method for preparing a single-atom catalyst loaded with Ir on a titanium oxide nanorod carrier rich in oxygen defects, the method comprising the following steps:

[0005] (S1) Preparation of defect-rich titanium oxide nanorod supports

[0006] Dissolving titanate in alcohol to obtain a mixed solution, immersing a substrate in the mixed solution, drying, and calcining in air at 300-500° C. for 1-3 hours to obtain a carbon fiber substrate with a titanium oxide seed layer;

[0007] Then, the substrate with the titanium oxide seed layer is mixed with titanate and acid, and subjected to hydrothermal reaction at 140-170° C. for 8-20 hours, and then washed, dried, and calcined at 500-900° C. for 3-8 hours in a hydrogen and argon atmosphere to obtain a defect-rich titanium oxide nanorod carrier;

[0008] Wherein, the titanate is selected from butyl titanate, titanium isopropoxide, titanium tetrachloride, titanium sulfate; the alcohol is selected from isopropanol, ethanol, methanol; the substrate is selected from carbon fiber, carbon paper, conductive glass;

[0009] (S2) Preparation of supported catalyst

[0010] The defect-rich titanium oxide nanorod support prepared in step (S1) is immersed in a 0.1-0.75 mg / mL chloroiridic acid solution, left for 3-6 hours, dried, and calcined at 200-500° C. for 1-3 hours under an inert atmosphere to obtain a single-atom catalyst loaded with Ir on the defect-rich titanium oxide nanorod support.

[0011] Wherein, the chloroiridic acid solution is a solution of chloroiridic acid in an ethanol solution, a methanol solution, an isopropanol solution or other volatile solvent.

[0012] According to the present invention, the defect-rich titanium oxide nanorod support can be TiO 2-x It represents that, wherein x can be, for example, 0.0001 to 0.4; preferably, x is 0.0005 to 0.1, and more preferably, 0.001 to 0.05.

[0013] According to the above preparation method, a single-atom catalyst loaded with Ir can be prepared on a defect-rich titanium oxide nanorod carrier. After oxygen vacancies are introduced into the titanium oxide carrier, the Ir single atom cooperates with the oxygen vacancies to activate the activity of the inert Ti site, thereby improving the intrinsic activity of the catalyst. The titanium oxide carrier used in the present invention can exist stably in an acidic environment, and there will be no problem of carbon corrosion in most carbon carriers used in an acidic environment for a long time.

[0014] When preparing a carbon fiber substrate with a titanium oxide seed layer in step (S1), the content of titanate and alcohol is not particularly limited. Generally, the alcohol is excessive so that the titanate can be fully hydrolyzed. Considering the amount of seeds formed on the carbon fiber substrate and the cost and other factors, the volume ratio of titanate to alcohol is 1: (10-100), preferably 1: (30-70), and more preferably 1: 40.

[0015] When preparing the defect-rich titanium oxide nanorod carrier in step (S1), the content of titanate and acid is not particularly limited, as long as the desired titanium oxide nanorod carrier can be prepared; considering the prepared defect-rich titanium oxide nanorod carrier and cost factors, the volume ratio of titanate and acid is 1: (30-200), preferably 1: (70-130), and more preferably 1: 100.

[0016] In the above preparation method, preferably, in step (S1), the concentration of the acid is 3 to 6 M; the temperature of the hydrothermal reaction is preferably 150°C to 160°C; and the calcination temperature in the hydrogen-argon atmosphere is 500°C to 700°C.

[0017] In the above preparation method, preferably, in step (S2), the concentration of chloroiridic acid is 0.1 to 0.6 mg / mL.

[0018] In the above preparation method, preferably, in step (S2), the calcination temperature is 200°C to 400°C.

[0019] In the above preparation method, preferably, in step (S2), the inert atmosphere refers to nitrogen, argon, helium or a mixed atmosphere thereof.

[0020] According to one embodiment of the present invention, the method comprises the following steps:

[0021] (1) Preparation of defect-rich titanium oxide nanorod carriers:

[0022] Butyl titanate was dissolved in isopropanol (the volume ratio of butyl titanate to isopropanol was 1:40), and then the carbon fiber substrate was immersed in the above-mentioned mixed solution for 3 minutes, taken out, dried, and then baked at 400°C in an air atmosphere for 2 hours to obtain a carbon fiber substrate with a titanium oxide seed layer;

[0023] Secondly, the carbon fiber substrate with the titanium oxide seed layer was placed in a polytetrafluoroethylene reactor containing a mixture of butyl titanate and 3-6M hydrochloric acid (the volume ratio of butyl titanate to hydrochloric acid was 1:100), and then hydrothermally reacted at 150°C for 8 hours. After the reaction was completed, it was naturally cooled to room temperature, washed and dried; and further calcined at 700°C in a hydrogen and argon atmosphere for 4 hours to obtain a defect-rich titanium oxide nanorod carrier (TiO 2-x );

[0024] (2) Preparation of single-atom Ir-doped titanium oxide nanorod catalysts:

[0025] The titanium oxide nanorods prepared in step (1) are immersed in a 0.1-0.75 mg / mL chloroiridic acid ethanol solution for 3-6 hours, the titanium oxide nanorods rich in the immersion solution are taken out, dried, and calcined at 200-500° C. for 2 hours in an inert atmosphere to obtain a single-atom Ir-doped titanium oxide nanorod catalyst.

[0026] According to another aspect of the present invention, a single atom catalyst of Ir supported on a defect-rich titanium oxide nanorod carrier is provided, which is prepared according to the above method.

[0027] According to another aspect of the present invention, there is provided a use of the single-atom catalyst loaded with Ir on the defect-rich titanium oxide nanorod carrier in an electrocatalytic oxygen evolution reaction under acidic conditions.

[0028] Beneficial Effects

[0029] The present invention successfully introduces oxygen vacancies and doping Ir single atoms on the surface of titanium oxide nanorods, and the catalyst has excellent electrocatalytic oxygen evolution activity. Compared with commercial IrO2 nanoparticles, Ir single atoms highly dispersed on the surface of titanium oxide nanorods have the maximum utilization rate of precious metal atoms, which can expose more active sites, reduce the amount of precious metals, and reduce the cost of catalyst preparation; after further introducing oxygen vacancies in the titanium oxide carrier, Ir single atoms cooperate with oxygen vacancies to activate the activity of inert Ti sites, thereby improving the intrinsic activity of the catalyst. The catalyst of the present invention has the advantages of simple preparation method, safe and easy operation, and suitable for large-scale stable preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The single-atom Ir-doped TiO prepared in Example 1 2-x X-ray diffraction (XRD) patterns of the nanorod catalyst and the titanium oxide nanorods prepared in Comparative Example 1.

[0031] Figure 2 Electron paramagnetic resonance (EPR) spectra of the catalysts prepared in Example 1 and Comparative Example 2.

[0032] Figure 3 The single-atom Ir-doped TiO prepared in Example 1 2-x SEM image of the nanorod catalyst.

[0033] Figure 4 The single-atom Ir-doped TiO prepared in Example 1 2-x HAADF-STEM image of the nanorod catalyst.

[0034] Figure 5 This is the STEM image of Comparative Example 2. It can be seen from the figure that when there is no oxygen vacancy, Ir single atoms can still be obtained on the surface of titanium oxide nanorods.

[0035] Figure 6 XPS spectra of Ti 2p of the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2.

[0036] Figure 7 The single-atom Ir-doped TiO prepared in Example 1 2-x XPS spectrum of Ir 4f of nanorod catalyst.

[0037] Figure 8 OER linear sweep voltammetric polarization curves (LSV) of the catalysts prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 under acidic conditions.

[0038] Fig. 9 It is a graph showing the Tafel slopes of the catalysts prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4.

[0039] Fig.10 These are the EIS spectra of the catalysts prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4. DETAILED DESCRIPTION

[0040] The present invention is further described below in conjunction with the examples, which are only used to explain the present invention and are not intended to limit the scope of the present invention. The raw materials, reagents, and equipment required in the following examples and comparative examples are all commercially available.

[0041] Test equipment and methods:

[0042] The XRD test was carried out on a PANalytical X'Pert PRO XRD analyzer using Cu Kα radiation, a wavelength of λ=0.1542 nm, and a scanning speed of 5° / min.

[0043] SEM was performed on a Hitachi SU-8010 instrument.

[0044] HAADF-STEM was tested on a Themis Z instrument with an accelerating voltage of 200 kV.

[0045] The LSV polarization curve test was carried out in a three-electrode system using a Shanghai Chenhua CHI660E electrochemical workstation with a scan rate of 5 mV / s. -1 The test voltage range is 1-1.8V, and all electrode potentials in the polarization curves are corrected by manual iR compensation.

[0046] In the present invention, the hydrogen-argon atmosphere refers to a mixed atmosphere of hydrogen and argon, wherein the volume fraction of hydrogen is preferably 5%-10%, and the volume fraction of argon is preferably 90%-95%.

[0047] 1. Material preparation

[0048] Example 1

[0049] (1) Oxygen vacancy-rich titanium oxide nanorods (TiO 2-x ) is prepared: first, a titanium oxide seed layer is prepared on a carbon fiber (Taiwan Carbon Energy Carbon Cloth, WOS1011 type, 2cm x 3cm) substrate, comprising the following steps: dissolving butyl titanate in isopropanol (the volume ratio of butyl titanate to isopropanol is 1:40), and then immersing the carbon fiber substrate in the above-mentioned mixed solution for 2 minutes, taking it out and drying it, and then calcining it at 400°C in an air atmosphere for 2 hours to obtain a titanium oxide seed layer.

[0050] Secondly, the carbon fiber substrate on which the titanium oxide seed layer was grown was placed in a polytetrafluoroethylene reactor containing a mixture of butyl titanate and 6M hydrochloric acid (the volume ratio of butyl titanate to hydrochloric acid was 1:100), and then a hydrothermal reaction was carried out at 150°C for 8 hours. After the reaction was completed, it was naturally cooled to room temperature, washed and dried; and further calcined at 700°C in a hydrogen and argon atmosphere for 4 hours to obtain a defect-rich titanium oxide nanorod carrier.

[0051] (2) Single-atom Ir-doped TiO 2-x Preparation of nanorod catalyst: TiO prepared in step (1) 2-x The nanorods were immersed in a 0.5 mg / mL chloroiridic acid ethanol solution and placed for 4 h. The titanium oxide nanorods rich in the immersion solution were taken out, dried, and calcined at 300 °C in an argon atmosphere for 2 h to obtain single-atom Ir-doped TiO 2-x Nanorod catalysts.

[0052] Example 2

[0053] (1) Oxygen vacancy-rich titanium oxide nanorods (TiO 2-x ) is prepared as follows: The difference from Example 1 is that the calcination temperature in step (1) under a hydrogen and argon atmosphere is set to 600°C.

[0054] (2) Single-atom Ir-doped TiO 2-x Preparation of nanorod catalyst: according to Example 1.

[0055] Example 3

[0056] (1) Oxygen vacancy-rich titanium oxide nanorods (TiO 2-x ) was prepared as in Example 1.

[0057] (2) Single-atom Ir-doped TiO 2-x Preparation of nanorod catalyst: The difference from Example 1 is that the concentration of the chloroiridic acid ethanol solution is 0.1 mg / mL.

[0058] Comparative Example 1

[0059] (1) Preparation of titanium oxide nanorods: The difference from Example 1 is that the calcination in hydrogen and argon atmosphere is replaced by calcination in air, and the calcination temperature is 400°C.

[0060] In Comparative Example 1, the step of impregnating the chloroiridic acid solution to prepare the single atom catalyst was not performed.

[0061] Comparative Example 2

[0062] (1) Preparation of titanium oxide nanorods: The difference from Example 1 is that the calcination in hydrogen and argon atmosphere is replaced by calcination in air, and the calcination temperature is 400°C.

[0063] (2) Preparation of Ir-doped titanium oxide nanorod catalyst without oxygen vacancies: proceed as in Example 1.

[0064] Comparative Example 3

[0065] Commercial IrO2 catalyst (model 12030-49-8) produced by Henan Zijing, with a catalyst loading of 15 μg Ir / cm 2 .

[0066] Comparative Example 4

[0067] Commercial 20% Ir / C catalyst produced by Premetek, catalyst loading 15μg Ir / cm 2 .

[0068] 2. Material structure and composition analysis

[0069] Figure 1 The X-ray diffraction patterns (XRD) of Example 1 and Comparative Example 1 show that the titanium oxide nanorods prepared by hydrothermal and calcination contain two crystal phase structures, anatase and rutile, with the rutile phase being the main phase; while Ir doping does not affect the crystal phase structure of the titanium oxide nanorods, and no characteristic diffraction peaks related to Ir are observed, indicating the high dispersibility of Ir.

[0070] Figure 2 The electron paramagnetic resonance spectra (EPR) of Example 1 and Comparative Example 2. It can be seen from the figure that oxygen vacancies are successfully introduced into the titanium oxide nanorods after high-temperature calcination in a reducing atmosphere, and after doping with Ir, the oxygen vacancies still exist significantly.

[0071] Figure 3 The SEM image of Example 1 shows that titanium oxide nanorods were successfully prepared and Ir doping did not affect the TiO 2-x morphology;

[0072] Figure 4 This is the STEM image of Example 1. It can be clearly seen from the figure that Ir single atoms (bright spots) are evenly distributed on the surface of titanium oxide nanorods;

[0073] Figure 5 This is the STEM image of Comparative Example 2. It can be seen from the figure that when there is no oxygen vacancy, Ir single atoms can still be obtained on the surface of titanium oxide nanorods;

[0074] Figure 6 The XPS spectra of Ti 2p of Example 1, Comparative Example 1 and Comparative Example 2 show that after Ir doping, the characteristic peak position of Ti 2p shifts to high binding energy, indicating that there is a certain electronic interaction between the Ir single atom and the carrier;

[0075] Figure 7 The XPS spectrum of Ir 4f in Example 1 shows that the characteristic peaks at 62.25 and 65.14 eV are mainly attributed to Ir 4+ .

[0076] 3. Material performance test

[0077] The OER performance test of the material was conducted in a three-electrode system using a CHI 660 electrochemical workstation, with the catalysts of Example 1 and Comparative Examples 1-4 as working electrodes, Pt sheets as counter electrodes, Ag / AgCl as reference electrodes, and 0.1M HClO4 as an acidic electrolyte.

[0078] Figure 8 This is the OER linear sweep voltammetric polarization curve (LSV) of the catalyst under acidic conditions. It can be seen from the figure that the pure titanium oxide nanorods in Comparative Example 1 have almost no OER activity. When a small amount of Ir atoms are doped, its (Comparative Example 2) oxygen evolution overpotential is significantly reduced, indicating that Ir atoms are the main active substance; after further introducing oxygen vacancies into the catalyst, Example 1 is obtained. Compared with Comparative Example 2 without oxygen vacancies, the oxygen evolution overpotential of the embodiment is lower, the mass activity is higher, and the OER performance is further improved. This may be because the Ir single atom doping cooperates with oxygen vacancies to promote the activity of inert Ti sites. At the same time, the OER performance of Example 1 is significantly better than that of the commercial IrO2 in Comparative Example 3 and the Ir / C catalyst in Comparative Example 4, indicating that highly dispersed Ir single atoms can expose more effective active sites than nanoparticles. In addition, by Fig. 9 The Tafel slope and Fig.10 It can be seen from the EIS spectrum that Example 1, which simultaneously introduces oxygen vacancies and Ir single atom doping, has the lowest Tafel slope and the smallest impedance arc radius, indicating that its OER reaction kinetics is faster.

[0079] Table 1

[0080]

Claims

1. A method for preparing a single-atom catalyst loaded with Ir on a defect-rich titanium oxide nanorod carrier, the method comprising the following steps: (S1) Preparation of defect-rich titanium oxide nanorod supports Dissolving titanate in alcohol to obtain a mixed solution, immersing a substrate in the mixed solution, drying, and calcining in air at 300-500° C. for 1-3 hours to obtain a substrate having a titanium oxide seed layer; Then, the substrate having the titanium oxide seed layer is mixed with titanate and acid, and subjected to hydrothermal reaction at 140-170° C. for 8-20 hours, and then washed, dried, and calcined at 500-900° C. for 3-8 hours in a hydrogen and argon atmosphere to obtain a titanium oxide nanorod carrier rich in oxygen vacancy defects; Wherein, the titanate is selected from butyl titanate, titanium isopropoxide 、 Titanium tetrachloride, titanium sulfate; the alcohol is selected from isopropanol, ethanol, methanol; the substrate is selected from carbon fiber, carbon paper, conductive glass; (S2) Preparation of supported catalyst The defect-rich titanium oxide nanorod support prepared in step (S1) is immersed in a 0.1-0.75 mg / mL chloroiridic acid solution, left for 3-6 hours, dried, and calcined at 200-500° C. for 1-3 hours under an inert atmosphere to obtain a single-atom catalyst loaded with Ir on the defect-rich titanium oxide nanorod support, Wherein, the chloroiridic acid solution is an ethanol solution, a methanol solution, or an isopropanol solution of chloroiridic acid.

2. The method according to claim 1, wherein When preparing the substrate having a titanium oxide seed layer in step (S1), the volume ratio of titanate to alcohol is 1:(10-100); When preparing the defect-rich titanium oxide nanorod carrier in step (S1), the volume ratio of the titanate to the acid is 1:(30-200).

3. The method according to claim 1, wherein In step (S1), the concentration of the acid is 3-6M; the temperature of the hydrothermal reaction is 150°C to 160°C; and the calcination temperature under the hydrogen-argon atmosphere is 500°C to 700°C.

4. The method according to claim 1, wherein In step (S2), the concentration of chloroiridic acid is 0.1-0.6 mg / mL.

5. The method according to claim 1, wherein In step (S2), the calcination temperature is 200°C to 400°C.

6. The method according to claim 1, wherein In step (S2), the inert atmosphere refers to nitrogen, argon, helium or a mixed atmosphere thereof.

7. The method according to claim 1, wherein: The method comprises the following steps: (1) Preparation of defect-rich titanium oxide nanorod carriers: Dissolve butyl titanate in isopropanol, then immerse the carbon fiber substrate in the mixed solution for 1-10 minutes, take it out, dry it, and then bake it at 400°C in an air atmosphere for 2 hours to obtain a carbon fiber substrate with a titanium oxide seed layer; wherein the volume ratio of butyl titanate to isopropanol is 1:40; Secondly, the carbon fiber substrate with the titanium oxide seed layer was placed in a polytetrafluoroethylene reactor containing a mixture of butyl titanate and 3-6M hydrochloric acid, and then subjected to a hydrothermal reaction at 150°C for 8 hours. After the reaction was completed, it was naturally cooled to room temperature, washed and dried; and further calcined at 700°C in a hydrogen and argon atmosphere for 4 hours to obtain a defect-rich titanium oxide nanorod carrier; wherein the volume ratio of butyl titanate to hydrochloric acid was 1:100; (2) Preparation of single-atom Ir-doped titanium oxide nanorod catalysts: The titanium oxide nanorods prepared in step (1) are immersed in a 0.1-0.75 mg / mL chloroiridic acid solution and left for 3-6 hours. The titanium oxide nanorods rich in the immersion solution are taken out, dried, and calcined at 200-500° C. for 2 hours in an inert atmosphere to obtain a single-atom Ir-doped titanium oxide nanorod catalyst.

8. A single-atom catalyst of Ir loaded on a defect-rich titanium oxide nanorod carrier, prepared according to the method according to any one of claims 1-7. 9 . Use of the single-atom catalyst containing Ir on a defect-rich titanium oxide nanorod carrier according to claim 8 in an electrocatalytic oxygen evolution reaction under acidic conditions.